Processes and challenges associated with informal electronic waste recycling at Agbogbloshie, a suburb of Accra, Ghana. (November 2019) - Acquah, Augustine A.; D'Souza, Clive; Martin, Bernard; Arko-Mensah, John; Nti, Afua Amoabeng; Kwarteng, Lawrencia; Takyi, Sylvia; Quakyi, Isabella A.; Robins, Thomas G.; Fobil, Julius N.
Electronic waste (e-waste) is a worldwide problem in terms of increasing production rate in the global waste stream. Its recycling is known to be associated with adverse health outcomes. The recycling site at Agbogbloshie is a major e-waste recycling hub which presents enormous health threats to the residents in this community as a result of exposure to complex mixtures of chemicals associated with the poor work methods employed. This paper describes the processes involved in e-waste recycling at Agbogbloshie and discusses some of the associated health and psychosocial challenges. Direct field observations and in-depth interviews of eight e-waste workers were conducted from November, 2017 to December, 2017. Results from a thematic analysis of the data gathered; suggest that inappropriate recycling methods, financial constraints, and the high physical demands of e-waste recycling work were associated with adverse musculoskeletal health conditions among the workers. A more systematic ergonomic study is currently being undertaken to quantify the associations between physical work exposures and worker musculoskeletal health among e-waste workers in Agbogbloshie. Further studies that focus on locally adapted ergonomic interventions for effective recycling of e-waste and reducing the health risk to workers are needed.